Analisis Bentuk Lagu Nyanyian Penanian Dolo Berjudul “Allo Lendu’ Bulan Lendu’” - Rinda Lorensa Kombong; Slamet Haryono; Malarsih Malarsih (Ideas Publishing, 2023)
This research was conducted to analyze the structure of the song entitled